PROSES LEGALITAS GURU DAN UNIT TPA/TKA BKPRMI BERBASIS KOMUNIKASI KOLABORATIF DI KABUPATEN OGAN ILIR (STUDI PADA TPA/TKA KECAMATAN INDRALAYA DAN INDRALAYA UTARA) - Muhaimin, Ahmad; Farid, M. Mifta; Afriany, Deany; Juainah, Norma (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study discusses the legalization process of teachers and TPA/TKA BKPRMI units based on collaborative communication in Ogan Ilir Regency, specifically in Indralaya and North Indralaya Districts. This study uses the theory of